Fundamentals of structural analysis - Leet, Kenneth M. (McGraw-Hill Higher Education, 2008)
Fundamentals of Structural Analysis (originally published by Macmillan and newly updated) introduces engineering and architectural students to the basic techniques for analyzing most common structural elements, including beams, trusses, frames, cables, and arches. The book covers the classical methods of analysis for determinate and indeterminate structures, and provides an introduction to matrix formulation, the basis of computer analysis.